For the idea of good: multiple looks - Llanes Barbuzano, Rómula; Diviñó González, Esther (Rastros Rostros, 2017)
Introduction: the article aims to focus on the diversity of perceptions, representations, psychological and ethical positions, opinions and points of view that the idea of good can generate in an era that is globalizing at a rapid pace. The authors consider the class-public space of linguistic mediation between non-Spanish-speaking adults who learn Spanish as a foreign language in Cuba. Methodology: to study the manifestations of the evaluative attitudes in that context, a conversational model has been applied that overcomes the unilateral tendencies of educational influence. Results: the reflection has begun with the analysis of the types of oral and written texts produced in the communicative dynamic, which has been inseparable from the approach of complex notions, of permanent interconnection and generation as those of identity, interculturality, replicative character of the word, textuality, heteroglossia, inter and transtextuality of discourse. Conclusion: we reflect on the emergence of the voices and values of the other as a fundamental axiom that sustains the intercultural attitude of those who learn about the idea of good in a pluricultural classroom.